Variabel Penting dalam Meningkatkan Impulse Buying dengan Locus Of Control sebagai Moderasi - I.A. Oka Martini; Ni Made Margareta (Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2026)
This study aims to determine the effect of Shopee Paylater and shopping lifestyle on locus of control, as well as to examine the moderating role of impulse buying in the relationship between Shopee Paylater, shopping lifestyle, and locus of control. The sample in this study consisted of 110 individuals. The data analysis technique used was PLS 4. The results of the study showed that Shopee Paylater has a positive and significant effect on impulse buying, shopping lifestyle has a positive and significant effect on impulse buying, locus of control positively and significantly moderates the relationship between Shopee Paylater and impulse buying, and locus of control positively and significantly moderates the relationship between shopping lifestyle and impulse buying. The researcher recommends that Shopee offer more attractive promotions for the use of Shopee Paylater when shopping online, to encourage users to use Shopee Paylater more frequently, provide features that bring enjoyment during shopping, and ensure all products needed by consumers are available. Furthermore, it is important to always provide all the products that consumers need to encourage spontaneous purchases and offer more attractive promotions to encourage purchases without thorough consideration.